Secondary sideband harmonic emission characteristics of individual/multi-parallel grid-connected inverters - Shaobo Xu; Shun Tao; Yonghai Xu (International Journal of Electrical Power & Energy Systems, 2025)
The analog/digital (A/D) sampling and the pulse width modulation (PWM) processes of grid-connected inverters have sideband effects. Under the influence of sideband effects, the interaction between background harmonics in the distribution network and grid-connected inverters will generate a series of secondary sideband harmonics, which result in significant increase of harmonic pollution sources in the distribution network. The frequency coupling effects among secondary sideband harmonics of an individual grid-connected inverter, as well as the secondary sideband harmonic interactions among multi-parallel grid-connected inverters significantly complicate the harmonic emission characteristics of grid-connected inverters. This paper focuses on the analysis of secondary sideband harmonic emission characteristics of individual/multi-parallel grid-connected inverters under background harmonic distortion. The secondary sideband harmonic current models of the individual/multi-parallel grid-connected inverters are proposed respectively. With the proposed models, the secondary sideband harmonic emission characteristics of an individual grid-connected inverter are studied. The impacts of the number of paralleled inverters, LCL parameters, control parameters and asynchronous carrier conditions on secondary sideband harmonic interaction between multi-parallel grid-connected inverters are revealed. The physical experiment results validate the developed secondary sideband harmonic models of individual/multi-parallel grid-connected inverters.